Effects of Chelated Iron (Eddha-Fe) Treatments on Corm And Stigma Quality in Saffron (Crocus Sativus L.) - Asil , Hasan (Bangladesh Journal of Botany, 2023)
Effects of different doses of chelated iron (EDDHA-Fe) on the yield and quality of saffron leaf, corm and stigma were investivated. The highest weight of harvested corms was obtained when treated with 2 g of iron chelate per corm, 366.57 g, and the highest number of corm was obtained when treated with 4 g of iron chelate per corm, 73.00 g. When the effects of the iron chelate treatments on the quality of the stigma studied, it was found that the treatment with 2 g of iron chelate per corm gave a yield of dry stigma 754.00 mg and the highest average amount of safranal of 1386.50 mg/kg. The treatment with iron chelate had a positive effect in increasing the yield of the corm, the yield of dry stigma, and the quality of stigma saffron. Bangladesh J. Bot. 52(1): 97-103, 2023 (March)